The Efficacy of Educational Videos on Perineal Wound Care Using Red Betel Extract Salve in Enhancing the Knowledge and Attitudes of Postpartum Mothers for Improved Healing - Fratidhina, Yudhia; Mulyati, Sri; Astri, Hetty; Mulyana, Nana; Sari, Gita Nirmala (Journal of Midwifery, 2024)
This study examines how an educational program combined with red betel extract salve application affects postpartum mothers' knowledge and attitudes toward perineal care, focusing on Grade 2 perineal lacerations. With 80 participants split evenly between intervention and control groups, those in the intervention group received education and salve application, leading to significantly improved knowledge and attitudes compared to the control group, which followed standard care protocols. Specifically, the mean knowledge score for the intervention group increased from 7.48 to 9.70 post-intervention, while the control group's knowledge score remained stable at 7.08 (p < 0.001). In terms of attitudes, the intervention group displayed a significantly more positive attitude, with a mean attitude score of 39.12 post-intervention, compared to the control group's score of 35.52 (p < 0.001). These results highlight the potential of educational interventions to substantially improve both knowledge and attitudes related to perineal care among postpartum mothers. These findings contribute to advancing postpartum care practices, benefiting the overall well- being of postpartum mothers during this pivotal stage of their maternal journey.